INCLUSIVISM AND EXCLUSIVISM AS WELL AS THEIR EFFECT ON ISLAMIC EDUCATION BASED MULTICULTURAL - Dhikrul Hakim (The Islamic Education and Multiculturalism Foundation, 2019)
Abstract. The majority of Indonesia's population embraces Islam, there are some of other religions and beliefs that are also recognized and adhered to by residents in this country, Christians, Catholics, Hindus, Buddhists and Confucians. Indonesian society is a society with a very complex level of diversity, the diversity is known as a multicultural society. This implies that without media in the form of education, plural theology will be difficult to develop in Indonesia. With education, we can have strong basics in understanding differences because essentially education is a process of